The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/en9080587
|View full text |Cite
|
Sign up to set email alerts
|

Realizing the Intended Nationally Determined Contribution: The Role of Renewable Energies in Vietnam

Abstract: Abstract:This study contributes to the realization of intended nationally determined contributions (INDCs) by analyzing their implications for the energy production system and the economy, and determines the role of renewable energies (RE) in reducing the challenge of committing to the INDCs. The Asia-Pacific Integrated Model/Computable General Equilibrium (AIM/CGE) model was used to assess seven scenarios having the same socioeconomic development but different shares of RE in power generation. By comparing di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…In general, this result showed that the energy reform could increase the use of gas and renewable energy, relatively more environmentally friendly than those of coal and oil. This result reflects those of [3,4,6,44] who stressed the benefit of phasing out energy subsidy on clean energy transition and later extended as one of the dominant strategies for carbon emission reduction. Without specific re-allocation in renewable energy, the share of this energy could increase from 0.16% (SIM 3) to 0.18% (SIM 1 and SIM2).…”
Section: The Impact On Energy MIXsupporting
confidence: 79%
See 1 more Smart Citation
“…In general, this result showed that the energy reform could increase the use of gas and renewable energy, relatively more environmentally friendly than those of coal and oil. This result reflects those of [3,4,6,44] who stressed the benefit of phasing out energy subsidy on clean energy transition and later extended as one of the dominant strategies for carbon emission reduction. Without specific re-allocation in renewable energy, the share of this energy could increase from 0.16% (SIM 3) to 0.18% (SIM 1 and SIM2).…”
Section: The Impact On Energy MIXsupporting
confidence: 79%
“…Energy transition, from fossil-based to zero-carbon energy, has been a tremendous global concern in the Paris Agreement objective [1], as energy consumption is the most significant contributor to the increasingly growing emission. The transformations towards renewable energy and energy efficiency are essential strategies required for carbon reduction [2][3][4]. Countries implement various measurements to encourage energy transition.…”
Section: Introductionmentioning
confidence: 99%
“…The model is specified and solved as a pure mixed complementary problem (MCP). There is a national version of this model, which was used for this study [17][18][19][20][21].…”
Section: Modelmentioning
confidence: 99%
“…Among such CGE models, AIM/CGE has unique characteristics in its detailed representation of agriculture, land, and energy supply sectors. In addition, AIM/CGE has been used for Asian-specific analyses [20,25,26].…”
Section: Modelmentioning
confidence: 99%